Estimation of immunoglobulin concentration IgM, IgG, IgA in blood serum after operatinons in different areas of the abdominal cavity in perimenopausal women - Szczęśniak, Grzegorz; Kotarski, Jan; Sikora-Szczęśniak, Dobrosława; Rojewski, Robert J. (Menopause Review/Przegląd Menopauzalny, 2005)
The aim of this work was to evaluate and compare immuglobulin concentration of IgG, IgA and IgM before treatment, in the first and tenth twenty-four hours among patients in three groups after laparascopic cholecystectomy, classic cholecystectomy and abdominal hysterectomy. Apart from higher IgM concentration in the first twenty-four hours after laparoscopy, we did not observe significant differences between IgM, IgA, IgG concentration in blood serum after removing the cholecystectomy by laparoscopy or in a classical way. In comparison to concentrations noted among women after hysterectomy lower concentration of IgM in the first twenty-four hours after the operation removing the cholecystectomy through laparotomy and in tenth twenty-for hours after removing the cholecystectomy both through laparotomy and laparoscopy.